23rd AIAA/CEAS Aeroacoustics Conference 2017
DOI: 10.2514/6.2017-4043
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Shock Formation in Noise Propagation During Ground Run-Up Operations of Military Aircraft

Abstract: A distinctive feature of many propagating, high-amplitude jet noise waveforms is the presence of acoustic shocks. Metrics indicative of shock presence, specifically the skewness of the time derivative of the waveform, the average steepening factor, and a new wavelet-based metric called the shock energy fraction (SEF), are used to quantify the strength and prevalence of acoustic shocks within waveforms recorded 10-305 m from a tethered military aircraft. The derivative skewness is more sensitive to the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…Evidence for cumulative nonlinear propagation effects for the tied-down F-35 is presented in Refs. [48,49]. The differing high-frequency slope confirm what was reported for a different aircraft engine's noise in Ref.…”
Section: B Errorssupporting
confidence: 88%
See 3 more Smart Citations
“…Evidence for cumulative nonlinear propagation effects for the tied-down F-35 is presented in Refs. [48,49]. The differing high-frequency slope confirm what was reported for a different aircraft engine's noise in Ref.…”
Section: B Errorssupporting
confidence: 88%
“…This combination region extends to approximately 105°, after which the addition of FSS spectrum no longer improves the agreement, and the LSS spectrum matches all except the high frequencies ( Figure 5(b)), which have elevated levels due to nonlinear propagation [48,49]. In the maximum radiation region (inlet angles approximately 110°-140° at 75% ETR), the LSS spectrum captures the overall shape of the peak region of the PSD (Figure 6(a)), but misses several important features: 1) multiple spectral peaks [43,44,45], 2) shallower high-frequency slope (of 1/ K ) resulting from nonlinear propagation [36,37,38,39,48,49], and 3) steeper low-frequency slope. All three features were noted in prior spectral decompositions of high-performance military aircraft [14,15,33], and are discussed in more detail in Sec.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Notably, it is well established that the sound waves they generate are strong enough to be affected by nonlinear distorsions. 6,7 These nonlinear effects cumulate during propagation, leading to the progressive formation of shocks, as observed in measurements performed in the acoustic far fields of military jet aircrafts, 8 as well as in numerical simulations. 9 However, estimations of the propagation distances required for shock formation have shown that, in some cases, steepened waveforms were found too close from the jet to be only the result of nonlinear propagation effects.…”
Section: Introductionmentioning
confidence: 83%